Optimization of direct methods for the approximate solution of weakly singular integral equations - Urumbaev, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For a class of weakly singular integral equations with power and logarithmic singularities, we establish the optimal order of the error of direct methods and indicate the procedure which realizes this order.